Assessment of arsenic contamination in tube-well drinking water in Hanam province - Bui Huy Tung; Tran Thi Tuyet Hanh; Hung Nguyen-Viet (2013)
An environmental health risk assessment was performed to describe the arsenic contamination in tube-well water and assess the health risks of people in Chuyen Ngoai commune, Duy Tien district, Ha Nam province. A total of 150 households were included in the study and results showed that most of the tube-well drinking water samples were contaminated with arsenic (98.7% of the samples before filtration and 80.4% ones after filtration).The concentrations of arsenic in the tube-well water before filtration were high, (mean? 301.1 ppb). The majority of households (95.3%) designed the water filters themselves or followed the model of their neighbours. The average filtration efficiency was high (89.3%). However, the average concentration of arsenic in water after filtration was 26.5 ppb, which was 2.65 times higher than the Ministry of Health’s standard level for the drinking water (QCVN 01-2009 BYT). Most of the filters did not meet the established standards for adequate filtration, including the technical standard for thickness (95.3%) and appropriate filter replacement/cleaning techniques (66.9%). Most of the households had no aeration systems (90.5%). Twenty-four hair samples (16%) had arsenic levels higher than the standard accepted level. Six hair samples (4%) were higher than 0.8 mg/kg, the diagnostic standard for chronic arsenic poisoning. In 60% of adults, the daily intake of arsenic was lower than the established TDI level (1 µg/kg/day). The average risk of cancer in adults due to consuming filtered tube-well drinking water was 23.5 x 10-5. This cancer risk is increased by 1.2 and 1.5 times after five and 10 years of drinking filtered water, respectively. This study shows the high contamination levels of arsenic in tube-well water in Hanam. Improved filtration measures or replacement of the current drinking water sources to reduce or prevent drinking water contamination with arsenic is recommended.